The Computing as a transversal axis in the administration degree (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2022)
The present investigation aims to promote at the different levels of the study plan of the administration career the transversal insertion of informatics for the achievement of characteristic learning, pertinent to the changes that are taking place in labor matters, promoting the need for a renewal in the curricular units that show in their programmatic contents the need for the use of information technology, through the systematic development of learning processes and technological procedures used in the various activities of the different areas of knowledge of the main axis of the Administration program of the Deanship of Economic and Business Sciences (DCEE) from the Universidad Centroccidental Lisandro Alvarado (UCLA). Exploratory and field research, with the support of the bibliographic review, procedures and regulations. Methodologically, the work is based on the competency-based curricular model and will be developed in three phases: a first phase where the curriculum will be analyzed through the different study programs in order to know which curricular units are the most appropriate to include the computing. A second phase of analysis of internal relevance taking into account the coordinating teachers responsible for the curricular units of the Administration career to indicate where and how to include strategies for the use of information technology. Finally, if the proposal is implemented, it will be possible to establish an articulation between informatics and the subjects of the subjects in the strategies of the study programs of the administration axis, contributing to the formation of integral professionals.
Keywords: administration career; informatics; cross-curricular axes